Miejsce CSR w europejskiej strategii na rzecz zrównoważonego rozwoju - Lewicka-Strzałecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2009)
The idea of Corporate Social Responsibility is a priority for the European economy because CSR is promoted by the European Commission as an instrument of European strategy for sustainable development. The paper presents the basic assumptions of this strategy. Although the debate on the European shape of CSR was initiated almost ten years ago some important questions are still under discussion. The paper considers some of them.